1941 Hercules Advertisements - Hercules Incorporated (1941)
The extensive collection of Hercules advertising materials, covering the years 1913 through 1952, documents the company's growth as a major manufacturer of chemical products. A portion of the 1941 edition is digitized here with content covering a range of products, including pine oil, terpenes, explosives, and blasting supplies.
Keywords: Chemical industry; Hercules Incorporated; Pine oil; Terpenes; Corporations; Naval stores; Explosives industry; Advertising, Industrial